Long Non-Coding RNA TPTEP1 Exerts Tumor Suppressive Functions via Sequestering miR-4295 to Regulate Growth Arrest and DNA Damage-Inducible 45α Expression in Acute Myeloid Leukemia - Liu X; Gui Y; Wang C; Xia K; Yang P (Cancer Management and Research, 2025)
Xueni Liu, Yonghui Gui, Chao Wang, Kang Xia, Peng Yang Department of Blood Transfusion, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230001, People’s Republic of ChinaCorrespondence: Peng Yang, Department of Blood Transfusion, The First Affiliated Hospital of Anhui Medical University, 218 JiXi Road, Hefei, 230001, Anhui, People’s Republic of China, Tel/Fax +86-55165908621, Email yangpeng@ahmu.edu.cnIntroduction: Recent evidences show that long non-coding RNA (lncRNA) plays an essential role in physiology and pathophysiology. The purpose of this study was to determine the role and its potential underlying mechanisms of the lncRNA transmembrane phosphatase with tensin homology pseudogene 1 (TPTEP1) in acute myeloid leukemia (AML).Methods: We detected the TPTEP1 and miR-4295 expression levels in AML cells. The vitro effects of TPTEP1 and miR-4295 on AML cells were analyzed. The correlation between miR-4295 and TPTEP1 or Growth arrest and DNA damage-inducible 45α (GADD45α) was confirmed by a luciferase reporter assay and RNA immunoprecipitation. The expression of GADD45α was investigated by Western blotting.Results: TPTEP1 was down-regulated in AML cell lines and AML patients. Ectopic expression of TPTEP1 inhibited AML cells proliferation while promoted cells apoptosis. And we found that silencing miR-4295 produced the similar effect of TPTEP1 overexpression. TPTEP1 regulated the malignant behavior of AML cells by binding to miR-4295. In addition, overexpression of TPTEP up-regulated GADD45α, a direct target of miR-4295 which play a suppressive role in AML cells. Moreover, when AML cell lines were treated with a DNA methylation inhibitor, TPTEP1 expression was up-regulated.Conclusion: This study reveals that the lncRNA TPTEP1 regulates the expression of GADD45α by sponging miR-4295 in AML cells, which may represent a novel therapeutic target for AML.Keywords: acute myeloid leukemia, TPTEP1, miR-4295, GADD45α, methylation